King's shadow : [large type] a novel of king Herod's court - Hunt, Angela Elwell, 1957- (Hunt, Angela Elwell, 1957- Silent years., 2019)
"Two women occupy a place in Herod's court. The first, Salome, is the king's only sister, a resentful woman who has been told she is from an inferior race, a people God will never accept or approve. The second woman, Zara, is a lowly handmaid who serves Salome, but where Salome spies conspiracies and treachery, Zara sees hurting people in need of understanding and compassion. Powerful and powerless, Idumean and Jew, selfish and selfless--both women struggle to reach their goals and survive in Herod the Great's tumultuous court, where no one is trustworthy and no one is safe"--